A Move Towards Focused Parathyroidectomy in BSMMU Even Under Local Anesthesia (Bangabandhu Sheikh Mujib Medical University Journal, 2009)
Parathyroidectomy needs skill and experience for its tiny size and variation in number and location. The retrospective quasi-experimental study of 26 parathyroid operations was done in endocrine surgery unit of BSMMU during October 1994 to March 2007. All patients were within 31 to 50 years of age with female preponderance (M:F=1:5.5). All the patients had primary hyperparathyroidism diagnosed biochemically with variable rise of serum calcium and serum intact parathormone level and finally proved as single parathyroid adenoma after surgery. Different preoperative localization tests were done in 22 patients with positive impression in all except 2 (7.69%) sestamibi scan. The sestamibi scan showed 50% (2/4) negative impression which, later on, was proved as 100% false negative at surgery. Bilateral neck exploration (BNE) was done on 18 patients with 94.44% success of surgery and ‘focused' parathyroidectomy by unilateral neck exploration (UNE) was done on 7 patients of whom 4 underwent local anaesthesia with 100% success of gland removal. Temporary postoperative hypocalcaemia was observed in 22 patients. Full recovery from hypocalcaemia was in 20 (90.90%) patients though 2 (7.69%) patients with late diagnosis showed irreversible outcome not due to surgery but due to postoperative complex renal and cardiovascular deterioration. Focused parathyroidectomy can be safely done even under local anaesthesia in tertiary hospital. Key words: Primary hyperparathyroidism; preoperative localization; focused parathyroidectomy; local anaesthesia.DOI: 10.3329/bsmmuj.v2i1.3708 BSMMU J 2009; 2(1): 31-35